2002
DOI: 10.1152/ajpcell.01396.2000
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor regulation of uncoupling protein-1 mRNA expression in brown adipocytes

Abstract: García, Bibian, and Maria-Jesú s Obregó n. Growth factor regulation of uncoupling protein-1 mRNA expression in brown adipocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…Further studies are needed to identify changes in deiodinase activity or plasma thyroidstimulating hormone (TSH) levels after the switch to WD. The UCP1 expression in BAT was significantly increased after 72 h on WD, which is in line with increased body temperature after 72 h. T 3 is known to increase UCP1 expression in vitro (17) and to increase BAT UCP1 expression to normal levels in hypothyroid fetus (34). In this study, the increased T 3 levels in the WD mice may explain the increased UCP1 expression.…”
Section: Discussionsupporting
confidence: 76%
“…Further studies are needed to identify changes in deiodinase activity or plasma thyroidstimulating hormone (TSH) levels after the switch to WD. The UCP1 expression in BAT was significantly increased after 72 h on WD, which is in line with increased body temperature after 72 h. T 3 is known to increase UCP1 expression in vitro (17) and to increase BAT UCP1 expression to normal levels in hypothyroid fetus (34). In this study, the increased T 3 levels in the WD mice may explain the increased UCP1 expression.…”
Section: Discussionsupporting
confidence: 76%
“…Changes in mRNA and protein levels of Agt and Angptl4 were consistent. Among these, Agt and Egf may promote differentiation of preadipocytes 35, 36 and Angptl4 may inhibit fat deposition by depressing LPL activity 37 . Figure 8 showed that Agt directly inhibits the expression of Lep, Hmgcr, and Ldlr and Egf negatively regulates the expression of Lep.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the endogenous expression of markers of BAT activity, we found using antibody arrays that circulating FGF1 was regulated in a similar way to Ucp1 and Pgc1a in BAT, being induced by HFD and further potentiated by DAG and AZP531 treatment in HFD‐fed mice. FGF1 is increased by food intake and increases sympathetic efferent outflow, as well as having a direct effect on brown adipocyte UCP1 content (55).…”
Section: Discussionmentioning
confidence: 99%